2004
DOI: 10.1021/jm0342515
|View full text |Cite
|
Sign up to set email alerts
|

11β-Alkyl-Δ9-19-Nortestosterone Derivatives:  High-Affinity Ligands and Potent Partial Agonists of the Androgen Receptor

Abstract: We report the synthesis of novel steroidal androgen receptor ligands comprising 11beta-alkyl-Delta(9)-derivatives of 19-nortestosterone. These compounds are structurally related to the antiprogestin, antiglucocorticoid, and antiandrogen drug mifepristone (RU486). Nortestosterone analogues bearing 11beta-octyl and 11beta-decyl side-chains bind tightly to recombinant AR protein (IC(50) = 6.6 nM and IC(50) = 0.8 nM), block AR dimerization, exhibit activity against LNCaP prostate cancer cells, and comprise partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Studies by Muddana et al [29] have demonstrated that instead of using the steroidal core of mifepristone towards antiandrogen design, Δ 9 -19-nortestosterone chemical structure can be used as the core backbone, thereby eliminating antiglucocorticoid activity of the derivatives (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Muddana et al [29] have demonstrated that instead of using the steroidal core of mifepristone towards antiandrogen design, Δ 9 -19-nortestosterone chemical structure can be used as the core backbone, thereby eliminating antiglucocorticoid activity of the derivatives (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Alcohols 1a , 1r , 1t , 1u , 1v , 1w , 3a – 3e , 3h and 3i were purchased from Aldrich Co., Kanto Kagaku Reagent Division, Tokyo Kasei Kogyo Co., and Wako Pure Chemical Industries. Other alcohols ( 1b , 1c , 1d , 1e , 1f , 1g , 1h , 1i , 1j , 1k , 1l , 1m , 1n , 1o , 1p , 1q , 1s , 1v , 1x , 1y , 1a‐D , 3f , 3g ) and diol 5 were prepared according to the literature methods. NMR spectra were recorded on JEOL JNM‐AL400 FT‐NMR spectrometer (400 MHz for 1 H NMR and 100 MHz for 13 C NMR) and JEOL ECZ‐500 (500 MHz for 1 H NMR, 125 MHz for 13 C NMR and 470 MHz for 19 F NMR).…”
Section: Methodsmentioning
confidence: 99%
“…7). Along this line, studies by Muddana et al (2004) have demonstrated that instead of using the mifepristone as the core steroid backbone, D 9 -19-nortestosterone can be used as the core backbone for such 11b position analogs and Endocrine-Related Cancer (2006) 13 653-666 www.endocrinology-journals.org thereby eliminate the anti-glucocorticoid activity of the derivatives. Thus, we have used the available structural biology data to design D 9 -19-nortestosterone analogs, which should have high (i.e.…”
Section: Rationale For Cart Therapymentioning
confidence: 99%